My fair lady: a musucal play in two acts based on Pygmalion . - Lerner, Alan Jay, 1918-1986.; Shaw, Bernard, 1856-1950.; Candlelight Cabaret Theatre (Organization: Silver Spring, Md.); Richard L. Coe Theater Programs Collection (Library of Congress) (England Penguin Books, 1969)
Candlelight Cabaret Theatre presents "My Fair Lady," music by Frederick Loewe, lyrics by Alan Jan Lerner, adapted from "Pygmalion" by George Bernard Shaw, directed by Frank Johns, musical direction by Alan Rafel, choreography and musical numbers staged by Joy Hawkins, produced by Charles Fells, Bob Brenner, Irwin Lust.
Candlelight Cabaret Theatre, October 16, 1969-December 7, 1969.
"Candlelight Cabaret Theatre presents 'My Fair Lady' starring Bob Frankfurt, Jeannie Dougherty, Broadway's greatest musical show!"--Cover.
Title devised by Library staff.
Cast: Glenda Josiane, George Chapin, Elaine George, Jeannie Dougherty, Rodney Fayman, Fank Buckley, Bob Frankfurt, David Simon, David McCarter, Bob Brenner, Helen Jordan, Annette MacKinnon, Susan Axelrad, David Coon, Diane Covington.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Maryland -- Silver Spring; Theater programs -- 1969.